PENGARUH MOTIVASI DAN MINAT BELAJAR PESERTA DIDIK TERHADAP PRESTASI BELAJAR PADA MATA PELAJARAN EKONOMI MATERI PERDAGANGAN INTERNASIONAL KELAS XI IPS.2 DI SMA NEGERI 5 PADANGSIDIMPUAN TAHUN PELAJARAN 2020-2021 - Ali Nurdin Siregar; Raju Sihombing (Universitas Muhammadiyah Tapanuli Selatan, 2020)
This study aims to discuss, study, and see how the influence of students' motivation and interest in learning on learning achievement in Economics Subjects International Trade Material for Class XI IPS.2 at SMA Negeri 5 Padangsidimpuan Academic Year 2020-2021, the type of research used is Associative Research or Experimental Research. Associative research is research that aims to reveal or see the influence between two or more or more variables looking for the influence of variables on other variables. In this study the authors used Field Research Methods and Library Research. Based on the data analysis above using a double formula, it is obtained that the value of rcount is 0.592 by looking at the list of product moment labels with a sample size of 33, then consulted with the specified error of 5%, then the r table is 0.344. From this value, it can be seen that rcount is greater than rtable, namely 0.592> 0.344, then the alternative hypothesis (Ha) can be accepted and Ho can be rejected. So it can be accepted that it is accepted that the truth is accepted, it can be said that there is an influence of students' motivation and interest in learning on learning achievement in the subject of international trade material for class XI IPS.2 in SMA Negeri 5 Padangsidimpuan for the 2020-2021 academic year.